Inferring Hypogene Karst at Depth from the Patterns of Non-Tectonic Syncline Networks in Eocene Limestones, Western Desert, Egypt - Tewksbury, Barbara J.; Tarabees, Elhamy A.; Welch, Robert M.; Mehrtens, Charlotte J. (Frontiers in Earth Science, 2021)
Indirect indicators are critically important for recognizing hypogene karst that is too deep-seated to have explorable hypogene caves. We have suggested in previous publications that an extensive network of non-tectonic synclines in otherwise flat-lying Eocene limestone in Egypt might be such an indirect indicator. We proposed that synclines formed by sag of limestone layers overlying a zone of hypogene karst that today remains deep below the surface and suggested that hypogene speleogenesis resulted from ascending aggressive fluids associated with crustal extension and magmatism in Egypt during Red Sea Rift initiation. Without hypogene caves to explore, however, we were unable to provide compelling evidence for hypogene karst processes. By doubling our mapping area from 4000 km2 to 8000 km2, a clear picture has emerged of patterns in the syncline network that provide compelling evidence for hypogene speleogenesis. Over this larger area, the network displays two distinct patterns: 1) synclines and ridges that outline polygons 700-2000 m across, and 2) narrow N-S zones of synclines spaced 5-10 km apart, with WNW-ESE to NW-SE trending shallow synclines and ridges traversing the panels between N-S zones. The geometries suggest that the syncline network is controlled by two structural patterns in rocks underlying the limestones: 1) polygonal faults in underlying shales and 2) reactivated N-S, left-lateral basement faults that are largely blind at the current level of erosion. These structures served as conduits that conveyed fluids upward into the overlying Eocene limestones, triggering dissolution at depth and a pattern of sag above that was inherited from the nature and pattern of faults and fractures in rocks underlying the limestones. The unique patterns and characteristics of this network of synclines are applicable elsewhere as an indirect indicator of deep-seated hypogene karst. Our new data also strongly suggest that syncline formation spanned the time of crustal extension in Egypt associated with onset of Red Sea rifting ~23-22 Ma. Endogenic CO2 associated with mantle-derived basaltic magmas was likely a significant component of fluids, perhaps involving highly aggressive supercritical CO2. Mantle-derived C and He in modern Egyptian oasis water suggest that hypogene speleogenesis may still be locally active.